Pelvic node removal and disease-free survival in cervical cancer patients treated with radical hysterectomy and pelvic lymphadenectomy - Suprasert P. (2014)
Objective: To examine the relationship between the number of pelvic nodes removed and 5-year disease-free survival in early-stage cervical cancer patients who underwent radical hysterectomy and pelvic lymphadenectomy (RHPL). Methods: The medical records of 826 cervical cancer patients who underwent RHPL and who had at least 11 pelvic nodes removed at Chiang Mai University Hospital between January 2002 and December 2008 were reviewed. The patients were divided into 4 groups according to the number of nodes removed: 11-20 nodes (n = 243); 21-30 nodes (n = 344); 31-40 nodes (n = 171); and ≥ 41 nodes (n = 68). The 5-year disease-free survival of patients in each group was compared. The clinicopathological factors were analyzed using Cox regression to identify independent prognostic factors. Result: Five-year disease-free survival was not significantly different among the 4 groups. When patients with and without nodal involvement were considered separately, the 5-year disease-free survival in all groups was not significantly different. At multivariate analysis, the number of pelvic nodes removed was not an independent prognostic factor. Conclusion: The number of pelvic nodes removed was not associated with 5-year disease-free survival or number of positive pelvic nodes. © 2011 International Federation of Gynecology and Obstetrics. Published by Elsevier Ireland Ltd. All rights reserved.